A model of the impact of government revenue and the quality of governance on electricity and clean fuel use - Stephen G. Hall; Bernadette Ann-Marie O'Hare (Economies, 2025)
When governments have more revenue, they can invest in infrastructure, such as the provision of electricity or clean fuels, which is more effective in well-governed countries. Here, we use an equilibrium correction model to empirically investigate the relationship between government revenue per capita, six indicators of quality of governance, and the proportion of the population with access to electricity and clean fuels, using an unbalanced panel dataset that includes nearly all countries in the world. The results suggest a strong effect over time: as government revenue increases, the provision of electricity and clean fuels increases, and the magnitude of this influence is mediated significantly by a country's quality of governance. This model offers the ability to demonstrate the impact of increases and decreases in government revenue in an individual country, while accounting for the impact of revenue on governance and on the provision of electricity and clean fuels.
Keywords: 330; electricity; clean fuels; sustainable development goals; government revenue; governance; government effectiveness; corruption